Match analysis in handball: A systematic review - Ferrari, W. R.; Sarmento, H.; Vaz, V. (Montenegrin Journal of Sports Science and Medicine, 2019)
The main objective of this research is to focus on a systematic review of the literature on handball, to identify potential areas for future research in this specific area of specialization. The most common research topics were identified, their methodologies were described, and the evolutionary tendencies of this area of research were systematized. Within a systematic review of the Web of Science ™ Core Collection, PubMed, and SportDiscus databases, according to the PRISMA guidelines, the following keywords were used: "handball", each one associated with the terms: "match analysis", "performance analysis", "notational analysis", "game analysis", "tactical analysis", and "patterns of play". Of the 245 studies initially identified, 28 were fully reviewed, and their results were analysed. Studies that meet all the inclusion criteria were organized according to the research design as descriptive, comparative, or predictive. The results showed that most of the studies use the statistics available through the tournament organization; some researchers have attempted to find some association between cause and effect in different contexts. The studies focused their analysis on four main variables of performance: total shots and finals, end match outcome, Time Outs (TTos), and the relationship between home advantage. This systematic review can provide useful information on potential lines of research for performance analysts in the field of handball match analysis.